2015
DOI: 10.1002/jcp.24899
|View full text |Cite
|
Sign up to set email alerts
|

Impaired expression of HIF-2α induces compensatory expression of HIF-1α for the recovery from anemia

Abstract: Erythropoiesis is strongly influenced by the interactions between stromal cells and erythroid progenitors, as well as by a key regulatory factor, erythropoietin (EPO). We previously generated mice with a knockdown mutation of Hif-2α (referred to as kd/kd) and found that these kd/kd mice exhibited normocytic anemia, even though the EPO expression was not severely affected. However, the VCAM-1 expression in spleen endothelial cells (EC), which is regulated by HIF-2α, was impaired, resulting in defective erythroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Increased hemolysis may be caused by dysfunction of RBCs correlated with (I) defects of Hb (hemoglobinopathies) (18, 94, 161, 199), including alterations in structure and function of Hb chains; (II) defects of cytoskeletal proteins such as spectrin and ankyrin, which are essential for maintaining cell shape and integrity (19, 134, 149, 169); (III) defects in metabolic enzymes catalyzing the pentose phosphate cycle (126, 147) such as deficiency of G6PDH; (IV) redox dysregulation and defects of antioxidant enzymes (63, 84); (V) presence of antibodies directed against surface antigens on RBCs, such as antibodies anti-A, or anti-B blood group antigens (formed as a consequence of transfusion of allogenic blood from the wrong blood group), or autoimmune antibodies resulting in enhanced damage of RBC membranes (14, 92, 124, 160, 164, 178); (VI) chronic inflammation, disorders of cytokine production, and chronic diseases (97, 105, 154); (VII) side effects of drug/poisoning (32); (VIII) other genetic defects (155, 187); or (IX) RBC extrinsic factors (102, 108, 113, 142, 180). Another important cause of anemia is the loss of RBCs due to acute or chronic bleeding (59).…”
Section: Rbc Dysfunction and Anemiamentioning
confidence: 99%
“…Increased hemolysis may be caused by dysfunction of RBCs correlated with (I) defects of Hb (hemoglobinopathies) (18, 94, 161, 199), including alterations in structure and function of Hb chains; (II) defects of cytoskeletal proteins such as spectrin and ankyrin, which are essential for maintaining cell shape and integrity (19, 134, 149, 169); (III) defects in metabolic enzymes catalyzing the pentose phosphate cycle (126, 147) such as deficiency of G6PDH; (IV) redox dysregulation and defects of antioxidant enzymes (63, 84); (V) presence of antibodies directed against surface antigens on RBCs, such as antibodies anti-A, or anti-B blood group antigens (formed as a consequence of transfusion of allogenic blood from the wrong blood group), or autoimmune antibodies resulting in enhanced damage of RBC membranes (14, 92, 124, 160, 164, 178); (VI) chronic inflammation, disorders of cytokine production, and chronic diseases (97, 105, 154); (VII) side effects of drug/poisoning (32); (VIII) other genetic defects (155, 187); or (IX) RBC extrinsic factors (102, 108, 113, 142, 180). Another important cause of anemia is the loss of RBCs due to acute or chronic bleeding (59).…”
Section: Rbc Dysfunction and Anemiamentioning
confidence: 99%
“…Importantly, although endogenous HIF-2 alone was shown to be inefficient in compensating for HIF-1 function during hypoxia [ 46 ], it has been also reported that in the absence of HIF-1, the exogenous HIF-2 was able to activate HIF-1-specific genes and vice versa [ 46 , 47 ]. Furthermore, in HIF-2α knockdown mice, HIF-1α regulates the expression of genes that are normally regulated by HIF-2α [ 48 ].…”
Section: Hif Target Genesmentioning
confidence: 99%
“…The expression pattern of HIF-1α, HIF-2α, and related gene targets within neurons and astrocytes may be co-dependent, with HIF and HIF-controlled target proteins synthesized in cells exerting a paracrine function 109 upon the other. Indeed, compensatory roles for both HIF-1α and HIF-2α have been described, 110 , 111 raising the question of how neurons are compensating by activating their own HIF-response system and if this is also affected by aging. Additionally, the balance of HIF-1α vs HIF-2α expression may shift when one or the other is diminished; however, we did not identify this in primary astrocytes in culture.…”
Section: Discussionmentioning
confidence: 99%